Microactuators and micromechanisms : proceedings of MAMM-2016, Ilmenau, Germany, October 5-7, 2016 /: proceedings of MAMM-2016, Ilmenau, Germany, October 5-7, 2016. ([2016]) - Unknown
No abstract available